W zgodzie z sobą i Ewangelią. Czy możliwy jest dzisiaj udany performans religijny? - Rotengruber, Przemysław (Człowiek i Społeczeństwo, 2022)
There is no doubt that the Catholic Church is in a deep crisis. On the one hand, it is internally divided between supporters of the changes initiated during the Second Vatican Council (1962–1965) and conservatives opposing these changes in the name of the (Counter-Reformation) decisions made during the Council of Trent (1545–1563). On the other hand, the Church is involved in a number of political, financial, paedophile, etc. scandals. They prove the progressive loss of contact of this institution with the world as a place to preach the Gospel. For both of these reasons, the number of believers in countries considered Catholic is steadily decreasing. The purpose of this article is to correct or supplement this diagnosis. Historically, the Catholic Church – like many other religious organizations – has never been „spotless”. However, this did not prevent Catholics from identifying themselves with this institution as the depository of the Revealed Truth. Today is different. Many of them are experiencing an identity crisis. They cannot reconcile the Gospel (which takes the form of religious dogma) with the existential and moral challenges they face every day. The subject of the research undertaken in this article is to find answers to the questions (1) about the skills that allow them to reconcile one with the other and (2) about the role of the Church in the education of the community of the faithful.